Step-by-step explanation:
the formula is :
tan (a+b) =
(tan (a) + tan (b)) / ( 1 - tan (a) . tan (b))
therefore
tan (π/5) + tan (π/2)) / (1-tan (π/5) tan (π/2))
= tan (π/5 + π/2)
Answer:
http://misterkmath.weebly.com/uploads/1/3/8/0/13802304/8-2d_answers.pdf
Step-by-step explanation: here is the answer sheet
Simplify
3
x
2
−
x
3
x
2
-
x
.
Tap for more steps...
x
2
=
x
10
−
4
5
x
2
=
x
10
-
4
5
Move all terms containing
x
x
to the left side of the equation.
Tap for more steps...
2
x
5
=
−
4
5
2
x
5
=
-
4
5
Since the expression on each side of the equation has the same denominator, the numerators must be equal.
2
x
=
−
4
2
x
=
-
4
Divide each term by
2
2
and simplify.
Tap for more steps...
x
=
−
2
Answer:
58
Step-by-step explanation:
First, draw out your triangle on a piece of paper, and label each point w, x, and y
We are then told that side wx and yw are similar. This means that we have an isosceles triangle with two similar sides.
We are also told that angle w is equal to 64 degrees
with this information, we can assume that angle y is the same as angle x
Another important thing to note is that all triangle measures equals to 180
SO
we can make this expression:
64 + x + x = 180
Now to solve for x:
64 + x + x = 180
64 + 2x = 180
2x = 116
x = 58
Answer:
The sequence above is a geometric sequence
For an nth in a geometric sequence
![u(n) = a {r}^{n - 1}](https://tex.z-dn.net/?f=u%28n%29%20%3D%20a%20%7Br%7D%5E%7Bn%20-%201%7D%20)
where n is the number of terms
a is the first term
r is the common ratio
From the question
a = 45
r = 15 / 45
The explicit formula for the sequence is
U(n) = 45(1/3)^n-1
Hope this helps you